The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.18608/jla.2014.11.6
|View full text |Cite
|
Sign up to set email alerts
|

Affective States and State Tests: Investigating How Affect and Engagement during the School Year Predict End-of-Year Learning Outcomes

Abstract: ABSTRACT:In this paper, we investigate the correspondence between student affect and behavioural engagement in a web-based tutoring platform throughout the school year and learning outcomes at the end of the year on a high-stakes mathematics exam in a manner that is both longitudinal and fine-grained. Affect and behaviour detectors are used to estimate student affective states and behaviour based on post-hoc analysis of tutor log-data. For every student action in the tutor, the detectors give us an estimated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(156 citation statements)
references
References 23 publications
6
121
0
9
Order By: Relevance
“…Baker, D'Mello, Rodrigo, & Graesser (2010) and Pardos, Baker, San Pedro, Gowda, & Gowda (2013) are examples of work using human annotated affective states. In Pardos et al (2013), the researchers used the Baker-Rodrigo Observation Method Protocol (BROMP) (Ocumpaugh, Baker, & Rodrigo, 2012) to correlate student behaviour and affect while participating in cognitive tutoring activities with performance on standardized tests.…”
Section: Human Annotated Affective Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Baker, D'Mello, Rodrigo, & Graesser (2010) and Pardos, Baker, San Pedro, Gowda, & Gowda (2013) are examples of work using human annotated affective states. In Pardos et al (2013), the researchers used the Baker-Rodrigo Observation Method Protocol (BROMP) (Ocumpaugh, Baker, & Rodrigo, 2012) to correlate student behaviour and affect while participating in cognitive tutoring activities with performance on standardized tests.…”
Section: Human Annotated Affective Statesmentioning
confidence: 99%
“…In Pardos et al (2013), the researchers used the Baker-Rodrigo Observation Method Protocol (BROMP) (Ocumpaugh, Baker, & Rodrigo, 2012) to correlate student behaviour and affect while participating in cognitive tutoring activities with performance on standardized tests. They found that the learning gains associated with certain affective states, namely boredom and confusion, are highly dependent on the level of scaffolding that the student is receiving.…”
Section: Human Annotated Affective Statesmentioning
confidence: 99%
“…Craig and colleagues [16] investigated the relationships between learning gains and affect state and found that confusion and flow were positively associated with learning gains but boredom was negatively associated with learning. Pardos and colleagues [30] also found that affect in intelligent tutors can predict not just local learning, but longer-term learning outcomes (state standardized exam scores) as well, specifically finding that boredom is negatively associated with longer-term learning outcomes while engaged concentration (e.g. flow) and frustration were positively associated with learning gains.…”
Section: Introductionmentioning
confidence: 97%
“…This work has generally found that a range of disengaged behaviors are associated with negative learning outcomes, including both gaming the system and off-task behavior [cf. 1,15,30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, data have been leveraged to increase student retention by creating an early-warning system to allow faculty to notify students who may be at risk of failing a particular course 19 . Also, data have been used to understand differences across students in online learning strategies to allow course designers to build a more personalized experience for different subgroups of learners 20,21 . With an increase in the number of available data sources, colleges and universities have a great opportunity to explore how data can shape, enhance, and direct learning at all levels.…”
Section: Literature Reviewmentioning
confidence: 99%